Development and characterization of locust bean gum-Viola anthocyanin-graphene oxide ternary nanocomposite as an efficient pH indicator for food packaging application. (December 2022) - Fathi, Morteza; Babaei, Amir; Rostami, Hosein
Abstract: The goal of this work was to introduce an eco-friendly pH-sensitive indicator for monitoring food freshness. In this regard, pH-sensitive locust bean gum (LBG) film containing 5 wt % of the extracted anthocyanin from Viola (VE) was fabricated. Subsequently, synthesized graphene oxide (GO) at the optimum concentration (0.5 wt %) was added to the film's formulation. It was revealed that incorporating GO into the neat LBG and LBG/VE films significantly enhanced the mechanical properties and thermal stability of the film (p<0.05). The LBG/VE/GO film showed a superior moisture content, water solubility, surface hydrophilicity and biosafety than LBG/VE film. The release study demonstrated a controlled release of VE from LBG/VE and LBG/VE/GO films over a period of 48 h. The antioxidant activity of LBG film significantly improved with the incorporation of VE (p<0.05). Overall, LBG/VE/GO film can be introduced as a smart packaging system to monitor the freshness of meat in real-time. Highlights: Locust bean gum (LBG) pH indicator film containing 5 wt % Viola extract (VE) and 0.5 wt % graphene oxide (GO) were fabricated. Addition of VE to the LBG matrix donated an appropriate pH-sensitivity to the fabricated film. Antioxidant activity of LBG film significantly enhanced by incorporating VE. Incorporation of GO into LBG matrix enhanced the mechanical properties and thermal stability of the film. Moisture content, water solubility, surface hydrophilicity and bio-safety of LBG-loaded VE film increased by GO addition.